Peepo! (Picture Puffin) - Ahlberg, Janet and Ahlberg, Allan (Penguin Putnam, 1999)
Here's a little baby One, Two, Three Stands in his Cot. What does he see? Peepo!He sees his father sleeping In the big brass bed and his mother too with a hairnet on her head.
Keywords: Juvenile literature-Children-Fiction